1967
DOI: 10.1037/h0025192
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative versus competitive concept attainment as a function of sex and stimulus display.

Abstract: Concept-attainment performance and strategies were compared for cooperative versus competitive pairs. A 2X2X2X5 repeated-measures factorial design was used with the following variables: instructions (cooperative or competitive), sex (male or female pairs), stimulus displays (form or sequence), and problems (5 for each pair). Major results were (a) Cooperative pairs had fewer card choices to solution, more use of focusing strategy, fewer untenable hypotheses, and more time to solution than competitive pairs; (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

1973
1973
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
2
19
1
Order By: Relevance
“…Raven and Eachus (1963) and Crombag (1966) used a task in which each subject's score was entirely dependent on the behavior of two teammates, and found far superior performance in subjects under a group reward contingency over those under an individual contingency. Hammond and Goldman (1961), Haines and McKeachie (1967), and Laughlin and McGlynn (1967) demonstrated greater group productivity in cooperative discussion groups than in competitive ones, whereas Scott and Cherrington (1974) have shown the opposite relationship with an independent task. However, several studies contradict the expectations of the Miller and Hamblin article.…”
Section: Reward Structures and Task Performancementioning
confidence: 70%
“…Raven and Eachus (1963) and Crombag (1966) used a task in which each subject's score was entirely dependent on the behavior of two teammates, and found far superior performance in subjects under a group reward contingency over those under an individual contingency. Hammond and Goldman (1961), Haines and McKeachie (1967), and Laughlin and McGlynn (1967) demonstrated greater group productivity in cooperative discussion groups than in competitive ones, whereas Scott and Cherrington (1974) have shown the opposite relationship with an independent task. However, several studies contradict the expectations of the Miller and Hamblin article.…”
Section: Reward Structures and Task Performancementioning
confidence: 70%
“…A review of research by Johnson and Johnson (1974) corroborated that the cooperative setting promotes intrinsic motivation in trat it leads to less anxiety, greater task involvement, and a more positive emotional tone (all characteristics of intrinsically motivated behavior) than does competition (e.g., Haines & McKeachie, 1967;Phillips & D'Amico, 1956). Several studies have shown that problem solving tends to be more effective and achievement tends to be greater under cooperative than under competitive conditions (e.g., Laughlin & McGlynn, 1967;O'Connell, 1965;Wodarski, Hamblin, Buckholdt, & Ferritor, 1973). Further, cooperative conditions seem to improve social adjustment and general cognitive development (e.g., Flavell, 1968;Johnson, 1975;Rothenberg, 1970).…”
Section: Intrinsically Motivated Learningmentioning
confidence: 97%
“…W. Johnson & Noonan, 1972); exchanging needed resources, such as information and materials, and processing information more efficiently and effectively (e.g., Crawford & Haaland, 1972; D. W. Johnson, 1974; Laughlin & McGlynn, 1967); providing efficient and effective help and assistance to group mates (e.g., D. W. Johnson & R. Johnson, 1989; Rosenbaum et al, 1980; Webb & Cullian, 1983); being motivated to strive for mutual benefit (Deutsch, 1949; D.…”
Section: Essential Elements Of Cooperationmentioning
confidence: 99%